Analysis of stress distribution in a thin rectangular plate by the method of caustics - Wang, J.; Batra, R.C.; Isogimi, K. (Archives of Mechanics, 1996)
We discuss some characteristics of caustics in a rectangular plate loaded by distributed in-plane loads on a part of two opposite edges with the other two edges kept traction-free. It is assumed that plane state of stress prevails in the plate. The theoretical developments are valid for an arbitrary location of the reflective plane within the plate. A good agreement is found between the computed and observed caustics. A simple inverse problem of determining the intensity of the distributed load from the size of caustics is also investigated.